Effects of dietary citric acid, lactic acid, and potassium sorbate mixture on growth performance and intestinal immunological parameters in common carp (Cyprinus carpio) juveniles - Seyyed Morteza Hoseini; Basim S. A. Al Sulivany; Alireza Afzali‐Kordmahalleh; Hamed Abdollahpour; Hamid Rajabiesterabadi; Morteza Yousefi (Journal of the World Aquaculture Society)
Abstract Acidifiers serve as effective feed additives that enhance fish growth and welfare. This study investigates the effects of a mixture of lactic acid, citric acid, and potassium sorbate (denoted as OA, in a 1:1:1 ratio) on common carp (Cyprinus carpio) for the first time. A total of 240 fish, each weighing approximately 18.5 grams, were randomly assigned to four treatment groups, each consisting of four replicates containing 15 fish. The fish were fed diets supplemented with varying levels of OA: 0 g/kg (Control), 2.5 g/kg (A‐2.5), 5 g/kg (A‐5), and 10 g/kg (A‐10) for a duration of 56 days. Growth performance, calcium and phosphorus levels in vertebrae and muscle, intestinal antioxidant status, bacterial populations, gene expressions, as well as immunological parameters in skin mucus and blood plasma were analyzed at the end of the experiment. The results indicated a significant (p < 0.0001) increase in the abundance of Lactobacillus sp. in the OA‐treated groups compared to the Control group. Conversely, the intestinal populations of Vibrio sp. (p < 0.0001) and Aeromonas sp. (p = 0.010) significantly decreased in the OA‐treated groups, particularly in the A‐10 treatment. Moreover, significant (p < 0.0001) up‐regulations were observed in the expression of intestinal tumor necrosis factor‐alpha (tnf‐a), interleukin‐1 beta (il‐1b), heat shock protein 70 (hsp70), and mucin‐2 (muc‐2) across all OA‐treated groups when compared to the Control group. All OA‐treated groups, especially the A‐5 treatment, exhibited significant (p < 0.0001) increases in the expression of intestinal lysozyme (lys), mucin‐5 (muc‐5), and beta‐defensin (b‐def) relative to the Control group. Furthermore, intestinal levels of reduced glutathione (GSH) significantly increased (p = 0.0003), while malondialdehyde (MDA) levels decreased (p = 0.002) in all OA‐treated groups, particularly in the A‐5 treatment. Notably, plasma lysozyme (p = 0.002), alternative complement (AC; p = 0.022), skin mucus protease (p = 0.011), lysozyme (p = 0.002), and alkaline phosphatase (ALP; p = 0.001) showed significant increases in the A‐5 and/or A‐10 treatments compared to the Control group. Dietary supplementation with OA significantly enhanced muscle and vertebral ash, phosphorus, and calcium levels, particularly in the A‐5 treatment. Additionally, growth performance and feed efficiency significantly improved in the A‐5 treatment when compared to the Control group. In conclusion, dietary supplementation with 5 g/kg of OA proved beneficial for common carp by enhancing intestinal health, humoral and mucosal immune responses, calcium and phosphorus retention, as well as overall growth performance.